A Mycological and Molecular Epidemiologic Study on Onychomycosis and Determination In Vitro Susceptibilities of Isolated Fungal Strains to Conventional and New Antifungals - Halvaee, Samaneh; Daie-Ghazvini, Roshanak; Hashemi, Seyed Jamal; Khodavaisy, Sadegh; Rahimi-Foroushani, Abbas; Bakhshi, Heidar; Rafat, Zahra; Ardi, Pegah; Abastabar, Mahdi; Zareei, Mahdi; Borjian-Boroujeni, Zeinab; Kamali Sarvestani, Hasti (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Onychomycosis is one of the most common and recurrent dermatological diseases worldwide. The antimycotic activity of prescribed medications varies according to the causative agents, and treatment failure rates exceeding 30%. This study aimed to assess the epidemiological profile of onychomycosis in Iran. Also, the susceptibilities to conventional and new antifungals were investigated. Methods: In this descriptive cross-sectional study, during the period of 18 months starting from September 2019 until March 2020, 594 nail specimens were obtained from patients who presented nail changes compatible with a clinical diagnosis of onychomycosis. All the samples were subjected to microscopic examination and fungal culture. Fungi identified were confirmed through the PCR-sequencing method. The susceptibility to itraconazole, fluconazole, terbinafine, griseofulvin, posaconazole, ravuconazole, efinaconazole, luliconazole, and tavaborole was evaluated according to the Clinical and Laboratory Standards Institute (CLSI) guidelines, document M38-A2 for filamentous fungi, and document M27-A3 for yeasts. Results: 594 patients were included. Of these, in 179 cases (30.1%) (95% CI:0.3±0.037) onychomycosis was confirmed. The majority of patients were ≥ 60 years of age (n=58, 32.6%) and female (n=113, 63.1%). Saprophytic fungi accounted for the vast majority of the nail isolates (n=92, 51.4%) (95% CI:0.051±0.0.073), followed by dermatophytes (n=45, 25.1%) (95% CI:0.25±0.063), and yeasts (n=42, 23.5%) (95% CI:0.23±0.061). Diabetes mellitus (77.3%), hypothyroidism (18.2 %), and solid tumors (4.5%) were documented as the most prevalent underlying conditions. Antifungal susceptibility testing was performed against 60 fungal isolates (20 each of Candida species, saprophytic fungi, and dermatophytes). Efinaconazole, ravuconazole, and luliconazole were the most active agents against Candida species. Also, luliconazole, posaconazole, and efinaconazole were most potent against dermatophytes. Luliconazole had the greatest antifungal activity against saprophytic fungi. Conclusions: The prevalence of onychomycosis in Iranian patients was relatively high. LUL exhibited potent antifungal activity against the three groups of fungi tested, determining its broad-spectrum antimycotic activity and its probable use as the first-line therapy for onychomycosis.